Strategi Guru Paud dalam Mengelola Kegiatan Pembelajaran Berbaris Kebutuhan Anak dan Hasil Pelatihan di TK Pelangi - Tio Rosalinda S. Pakpahan; Trina Dara Br Sinuraya; Yoel Panjaitan; Henni Shara Gracia Br Ginting (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This article explores the strategies used by early childhood teachers at TK Pelangi in managing learning activities based on children’s needs and the outcomes of training programs they have attended. The main focus is on how teachers apply training outcomes into daily classroom practice while adjusting to each child's developmental stage and individual characteristics. At TK Pelangi, teachers plan learning activities by considering each child’s interests, talents, and specific needs. In practice, they create a dynamic, enjoyable, and contextual learning environment to help children better absorb the material. Training outcomes are used as a foundation to develop more innovative methods, media, and approaches. Continuous evaluation is carried out to assess the effectiveness of the strategies. The findings show that managing learning based on children's needs and training results significantly improves the quality of teaching interactions and positively contributes to the overall development of children at TK Pelangi.